Studies on astral magic in medieval Jewish thought - Schwartz, Dov (Brill reference library of Judaism, 2005)
Astral magic is shown to be a major influence in Jewish medieval thought. The book traces its winding course in the work of such figures as Judah Halevi, Nahmanides and others, and provides a new perspective on medieval Jewish rationalism.